Prophylactic antibiotics for excision of premalignant vulvar lesions: A pilot randomized controlled trial - Mary M. Mullen; Whitney R. Grither; Hannah Millimet; David G. Mutch; Andrea R. Hagemann; Carolyn K. McCourt; Matthew A. Powell; Premal H.Thaker; Dineo Khabele; Lindsay M. Kuroki (Elsevier, 2024)
No prospective data have been described to inform guidelines on antibiotic prophylaxis for partial vulvectomies. Thus, we conducted a single-center, pilot, double-blind randomized controlled trial to assess the effectiveness of prophylactic antibiotics to prevent wound complications after partial vulvectomies. Patients were randomly assigned 1:1 to preoperative antibiotics or no preoperative antibiotics. The primary outcome of 30-day postoperative wound complications occurred in 31 (62 %) of all patients, with no differences between groups. The most common wound complications were superficial separation (54.2 % antibiotic prophylaxis vs. 65.3 % no prophylaxis, p = 0.37) and surgical site infection (0 % antibiotic prophylaxis vs 7.7 % no prophylaxis, p = 0.49). However, this study was limited by differences in patient characteristics between the groups. This study provides data to perform power calculations for a trial examining the effect of preoperative antibiotics on surgical site infection.